Efficiency Investigation of Coffee Production Waste Drying by Filtration Method - Oleksandr Ivashchuk; Volodymyr Atamanyuk; Roman Chyzhovych (Журнал інженерних наук)
This article presents the results of determining the technologically feasible parameters of filtration drying of coffee production waste based on experimental data on the kinetics of material drying and the hydrodynamics of thermal agent filtration. The lowest total energy costs were observed with the following process parameters: the material layer height of 120 mm, the thermal agent temperature of 90 °C, the velocity through the stationary layer of 1.76 m/s, and the specific energy consumption of 5857 kJ per 1 kg of water. Based on the determined technologically feasible process parameters, an evaluation of the filtration drying method for coffee production waste was performed at an industrial installation. According to the calculation, using the filtration method, 1164 kW h of energy was required to dry about 1000 kg of coffee production waste. A total energy of about 1.65 kW h/kg was required to remove 1 kg of moisture from the material in an industrial filtration drying installation. The results were compared with a drying material with similar initial parameters. It was calculated that to dry 1000 kg of coffee production waste in a rotary dryer, it is necessary to spend about 1625 kW h, and the total energy consumption for removing 1 kg moisture from the studied material is approximately 2.37 kW h/kg. Thus, for a similar output of about 1000 kg/h, filtration drying can reduce energy consumption by about 465 kW·h and reduce the required drying time by more than 20 times. The overall economic effect of using the filtration drying method in industry is expected to be higher, given the significant heat losses to the environment for a rotary dryer due to its large size, long drying time, design features, and the need for energy-intensive auxiliary equipment. After calculating the energy consumption per 1 kg of dry material, it is necessary to spend 12 950 kJ/kg of dry matter, about 41.5 % less than the higher calorific value for experimental samples of briquetted solid fuel made from this material. This result makes it economically feasible to further dry coffee production waste to produce alternative solid fuels.